The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4025/actasciagron.v33i4.11031
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of maize inbreds for kernel quality traits and fatty acid composition by a multivariate technique

Abstract: ABSTRACT. Quality is considered to be mainly related to protein and oil concentration in maize kernel. Great effort has been made through the elevation of oil and protein concentrations; however, studies to enhance the composition quality of oil have been limited. Maize genotypes with special fatty acid composition may confer different end uses and added value. We investigated eight maize inbreds for kernel quality and fatty acid composition. Kernel samples from a two-year experiment were analyzed for oil, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
14
0
5
Order By: Relevance
“…Thus, this method has commonly been used to evaluate combining abilities in maize breeding experiments in recent years (Mostavi et al, 2012;Badu-Apraku et al, 2013;Ruswandi et al, 2015). Additionally, the canonical discriminant analysis with yypothesis error (CDA-HE) plot has also been used to evaluate genotypes in breeding experiments for investigated traits (Egesel et al, 2011). Polar plot is a new method for heterosis analysis and gene action analysis (Lisec et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this method has commonly been used to evaluate combining abilities in maize breeding experiments in recent years (Mostavi et al, 2012;Badu-Apraku et al, 2013;Ruswandi et al, 2015). Additionally, the canonical discriminant analysis with yypothesis error (CDA-HE) plot has also been used to evaluate genotypes in breeding experiments for investigated traits (Egesel et al, 2011). Polar plot is a new method for heterosis analysis and gene action analysis (Lisec et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Turkey produces 2,200,000 tonnes annually of grain corn from about 575,000 ha of land (DaÈdelen et al, 2006). The food quality of corn products is directly related to the grain quality of the plant (Egesel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The typical maize kernel, on dry weight basis is composed of 61-78% of starch, 6-12% of proteins, 3.1-5.7% of oil, 1.0-3.0% of sugar and 1.1-3.9% of ash (Watson, 2003). In five different and recent studies on maize genotypes across the world protein content has been found to vary between 9.4-13%, 11.02-13.02%, 11.02-15.31%, 8.05-11.43% and 6.27-8.06%, while oil content has been found to vary between 3.32-4.70%, 2.56-5.57%, 4.39-9.71%, 3.80-5.02% and 2.7-5.2% respectively (Egesel et al, 2011, Aliu et al, 2012, Sanjeev et al, 2014, Scrob et al, 2014, Chibuike et al, 2015. In India, higher contents of oil (9.71%) and protein (15.31%) have been observed in sweet corn samples and attributed to shriveled grain texture because of an (Sanjeev et al, 2014) which is in consonance with our study.…”
Section: Resultsmentioning
confidence: 99%